2018
DOI: 10.3389/fphar.2018.01474
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of a Fixed Combination of Chinese Herbal Medicine in Chronic Urticaria: A Randomized, Double-Blind, Placebo-Controlled Pilot Study

Abstract: Background: Chronic urticaria is a bothersome skin disease, and Chinese herbal medicine (CHM) is commonly used as adjuvant therapy. This study aimed to evaluate the effectiveness and safety of the mixture of two CHM formula, Xiao-Feng-San (XFS) and Qing-Shang-Fang-Feng-Tang (QSFFT), in treating urticaria through a randomized, double-blind, placebo-controlled clinical trial.Methods: 78 participants entered the screening phase between November 2012 and August 2015. Participants were randomly and equally allocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Unfortunately, for patients that trial alternative medicine, their reported response rates are even lower with only 20-29% of patients reporting benefit in our study. This would be consistent with the inconclusive studies in acupuncture and traditional Chinese medicine [19][20][21][22][23]. Although, 21% of our patients reported visiting a naturopath, we could not find any studies in the literature that have studied the use of and effectiveness of naturopathic therapies in the treatment of CSU.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Unfortunately, for patients that trial alternative medicine, their reported response rates are even lower with only 20-29% of patients reporting benefit in our study. This would be consistent with the inconclusive studies in acupuncture and traditional Chinese medicine [19][20][21][22][23]. Although, 21% of our patients reported visiting a naturopath, we could not find any studies in the literature that have studied the use of and effectiveness of naturopathic therapies in the treatment of CSU.…”
Section: Discussionsupporting
confidence: 87%
“…There has been some studies that looked at acupuncture for global symptom improvement when used in conjunction with pharmacologic therapy however a recently published meta-analysis showed there is overall a low level of evidence for its use [19]. There has also been a few randomized trials that have looked at the use of traditional Chinese medicine as an adjunct to traditional pharmacologic therapy in CSU with varying results [20][21][22][23]. However, to our knowledge, there has not been any studies that have evaluated patient uptake of these alternative medicine practices and their perceived benefit.…”
mentioning
confidence: 99%
“…The dry root of Saposhikovia divaricata, also called 'Fang-Feng' , is a traditional Chinese herb that has anti-inflammatory and anti-allergic properties and is widely used as a drug in rheumatism, urticaria, and skin pruritus [9,10]. It is found that chromones are the major active ingredients in 'Fang-Feng' , consisting of Prim-oglucosylcimifugin and cimifugin [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yang et al [8] conducted and reported a pilot study on the effectiveness and safety of chronic urticarial in combination with Xiao-Feng-San and Qing-Shang-Fang-Feng-Tang.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a simultaneous quantitative analysis method was developed using 18 selected marker analytes for the quality evaluation of CSBPT based on HPLC separation combined with photodiode array detection (PDA). The selected components were prim-O-glucosylcimifugin (3) and 5-O-methylvisammioside (9) from Saposhnikoviae Radix, oxypeucedanin hydrate (13) from Angelicae Dahuricae, arctigenin (11) and arctiin (16) from Forsythiae Fructus, baicalin (12), wogonoside (14), and baicalein (15) from Scutellariae Radix, ferulic acid (7) from Cnidii Rhizoma, pulegone (18) from Schizomepetae Spica, geniposide (1) from Gardeniae Fructus, coptisine chloride (2) and berberine chloride (4) from Coptidis Rhizoma, narirutin (8) and hesperidin (10) from Aurantii Fructus Immaturus, and liquiritin apioside (5), liquiritin (6), and glycyrrhizin (17) from Glycyrrhizae Radix et Rhizoma.…”
Section: Introductionmentioning
confidence: 99%